The disparity of legal certainty in fiduciary guarantee execution following the Constitutional Court Decision Number 18/PUU-XVII/2019 based on a comparative study with Mortgage - Jamie Armadi Jaya; Henry Anderson Parapat; Faizal Achmad; Ananda Pradhitya Tenggara; Muhammad Viegri (Privietlab, 2026)
In rem security institutions are fundamentally established as mechanisms to safeguard investments by providing an Executorial Title to ensure the certainty of debt recovery. However, this landscape has undergone a paradigm shift following the Constitutional Court Decision Number 18/PUU-XVII/2019, which degrades creditors' rights and generates legal dualism between Fiduciary Guarantees and Mortgage Rights. Utilizing a normative legal research method with statutory and conceptual approaches, this article demonstrates that the Constitutional Court decision explicitly weakens fiduciary creditors tied to the doctrine of constitutum possessorium by transforming an independent parate execution process that once represented summary justice into a conditional execution mechanism that requires a written consensus on default and the voluntary surrender of the asset by the debtor. This alteration creates a strategic loophole for bad faith debtors, downgrades the status of the fiduciary certificate to a mere piece of ordinary civil evidence, and forces creditors into a prolonged and costly district court bureaucracy while exposing them to heightened moral hazards, such as the concealment or transfer of movable collateral. Furthermore, the comparative normative analysis identifies a sharp disparity that violates the principle of equality before the law and Aristotelian distributive justice, as fiduciary execution is paralyzed by procedural barriers while the Mortgage Law maintains its absolute and direct executorial title without judicial intervention. This imbalance completely disregards the economic characteristics of the collateral, in which movable fiduciary assets undergo rapid annual value depreciation compared to stable or appreciating mortgage objects, such as land and buildings. This means that execution delays caused by litigation cycles risk rendering the creditor's legal protection financially hollow.